European security strategy and its impact on the foreign policy of the European Union 1991-2020 (Journal of the College of Basic Education, 2026)
The importance of the research is evident in the study and analysis of the European Union's security strategy from a historical perspective, and a logical analysis of the developments of events after the Second World War 1939-1946. Due to the necessity of studying and discussing this strategy and its impact on international foreign policy, the topic was chosen, and the research was conducted in a foundational stage in the history of the European continent, especially since it coincided with international changes that resulted in a change in the global political map, after that period witnessed major global events such as the fall of the Berlin Wall in 1989, and the collapse of the Soviet Union in December 1991, which produced a purely European vision for unifying ranks. This matter contributed to changing some aspects of international politics, and this is what the research dealt with between 1991-2020, relying on sources from Ruhr University Bochum in Germany, and Black Sea Technical University in Turkey.